(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
In general terms, the variable penetration of RE in power systems has some inherent drawbacks, such as lack of manageability and resource variability [1]. Medium (in the range of minutes) and short term (in the range of seconds) variability has a negative impact on system reliability, causing a deterioration of system frequency quality in both interconnected and, moreover, isolated systems [1-2]. Specifically, the variability of the wave energy resource is medium- and short-term. Therefore, although wave energy could be very suitable to be integrated in islands due to its location, the variable nature of wave energy could negatively impact the stability of the power grid [3]. The case study of the work focuses on the island of El Hierro (Canary Islands, Spain). It is an isolated electrical system with a very high penetration of renewable energy sources. The generation of the electrical system is composed of a wind farm, a pumped hydroelectric power plant and conventional generation by means of a diesel power plant. In a previous analysis [4], the integration of energy storage systems based on flywheels was analyzed. Based on this previous analysis, the manuscript studies the influence of the integration of the wave energy park in the electrical system of El Hierro. On the one hand, a wave farm will be proposed to evaluate the generated power and its associated oscillation [5]. The wave energy resource at different locations along the coast of El Hierro will be taken into account. On the other hand, an aggregated inertial dynamic mode of the electrical power system will be used to evaluate the impact of the generated power on the electrical frequency and the aging/degradation effects of the hydropumping elements. The Spanish Grid Code will be taken into account regarding frequency regulation mechanisms in isolated systems. The degradation of the hydraulic pumping systems due to additional frequency regulation stresses and electrical frequency deterioration will be calculated and evaluated in relation to the penetration of wave energy into the system, with and without the flywheel energy storage plant. This will allow quantification of certain technical limits to wave energy penetration in isolated systems and to draw conclusions with reference to the size of such a power system. [1] R. S. Kaneshiro et al. “Hawaii Island (Big Island) Wind Impacts” Proc. of Workshop on Active Power Control from Wind Power, Broomfield, CO, USA, 2013. [2] H. R. Iswadi et al. “Irish power system primary frequency response metrics during different system non synchronous penetration,” IEEE Eindhoven PowerTech 2015, doi: 10.1109/PTC.2015.7232425. [3] Isabel Villalba et al. “Wave farms grid code compliance in isolated small power systems,” IET Renewable Power Generation, 2019, doi: 10.1049/iet-rpg.2018.5351. [4] Hilel Garcia-Pereira et al. “Comparison and Influence of Flywheels Energy Storage System Control Schemes in the Frequency Regulation of Isolated Power Systems,” IEEE Access, 2022, doi: 10.1109/ACCESS.2022.3163708. [5] M. Blanco et al. “Study of the impact of wave energy generation in the frequency of an island electric grid,” Proc. of the 12th European Wave and Tidal Energy Conference (EWTEC). 2017.